Australian dispensing doctors’ prescribing: quantitative and qualitative analysis - Lim, Chee; Emery, J.; Lewis, Jan; Sunderland, Bruce (Australasian Medical Publishing Company Pty. Ltd., 2011)
Objective: To evaluate the prescribing practices of Australian dispensing doctors (DDs) and to explore their interpretations of the findings.Design, participants and setting: Sequential explanatory mixed methods. The quantitative phase comprised analysis of Pharmaceutical Benefits Scheme (PBS) claims data of DDs and non-DDs, 1 July 2005 – 30 June 2007. The qualitative phase involved semi-structured interviews with DDs in rural and remote general practice across Australian states, August 2009 – February 2010.Main outcome measures: The number of PBS prescriptions per 1000 patients and use of Regulation 24 of the National Health (Pharmaceutical Benefits) Regulations 1960 (r. 24); DDs’ interpretation of the findings.Results: 72 DDs’ and 1080 non-DDs’ PBS claims data were analysed quantitatively. DDs issued fewer prescriptions per 1000 patients (9452 v 15 057; P =0.003), even with a similar proportion of concessional patients and patients aged > 65 years in their populations. DDs issued significantly more r. 24 prescriptions per 1000 prescriptions than non-DDs (314 v 67; P=0.008). Interviews with 22 DDs explained that the fewer prescriptions were due to perceived expectation from their peers regarding prescribing norms and the need to generate less administrative paperwork in small practices.Conclusions: Contrary to overseas findings, we found no evidence that Australian DDs overprescribed because of their additional dispensing role.